Potensi Simpanan Karbon Berdasarkan Struktur Tinggi Tanaman Pola-Pola Agroforestry di Kecamatan Tinggimoncong dan Parigi Kabupaten Gowa, Sulawesi-Selatan - Syamsuddin Millang (Biocelebes, 2010)
The study is aimed to (1) identify agroforesry pattern inside and outside of forest area based on structure and species composition; (2) know carbon stocks potential of agroforestry pattern base on vertical structure; (3) estimate aboveground carbon stocks of agroforesry patterns. The study was conducted on May to September 2009 in Tinggimoncong and Parigi District, Gowa Regency and Laboratory of Silvikultur, Hasanuddin University. To know tree biomass, measurement of diameter breast height was carried out. Total number of sample plots taken was 37 with 20 x 50 m in size. Selection and placement of sample plot was conducted by Purposive Sampling based on consideration of tree species dominant on each different agroforestry patterns. Withdrawal of tree’s biomass samples was conducted by non-destructive sampling, namely without destructing samples. The study results showed that (1) agroforestry system which generally used by community at the study location was agrisilviculture consisting of nine combination’s pattern of crop species. Interval adjustment follows random and border pattern with crop interval of tree component were irregular, (2) number carbon-stock on every range of vertical structure of agroforestry patterns were varied. Agroforestry Erythrina-jackfruit-coffee, clove-annual crops, african tree-coffee, Gmelina-banana patterns tend to follow bell-shaped curve or the stored carbon was the largest on medium-diamater trees, pine-vegetable, Eucalyptus-vegetable crops, pine-coffee, fruit trees-coffee tend to follow J-shaped curve or the stored carbon was the largest on wider-diameter trees, and agroforestry Erythrina-coffee patterns tend to be irregular; (3) two agroforestry patterns which had the highest potential carbon stocks aboveground were pine-coffee and fruittree-coffeeI agroforestry pattern amounted of 199.97 ton ha-1 and 100.54, respectively, and the lowest agroforestry pattern was clove-annual crop pattern namely 18.40 ton ha-1. Key words: Carbon stocks, agroforestry pattern, vertical stratification.